Inside special forces - Mackenzie, Richard; Mairesse, Emmanuel; National Geographic Television & Film.; Warner Home Video (Firm). (Burbank, Calif. : Warner Home Video, 2003)
Follow the US Special Forces into battle and on secret missions in Afghanistan and Iraq as they face situations where honed skill, finely tuned instincts and split-second decision making are the difference between life and death.
Keywords: Documentary television programs; Nonfiction films; Special forces (Military science).; Video recordings for the hearing impaired